A meta-analysis of change in applicants' perceptions of fairness - Udo Konradt; Martina Oldeweme; Sabrina Krys; Kai-Philip Otte (International Journal of Selection and Assessment, 2020)
Using an event-triggered multi-stage framework, this random-effects meta-analysis examined the changes in applicants' perceptions of fairness between consecutive stages and throughout the entire personnel selection process. We integrated findings of studies with at least two measurement points, resulting in 45 effect sizes (overall N~=~3,038). Trajectories of perceptions of fairness decreased nonlinearly across the process, with a steeper decrease for people who held high levels of initial fairness expectations. Unjust treatment produced a decrease in perceptions of fairness from pretest to posttest and an increase from posttest to postdecision. Furthermore, the length of the time interval moderated the changes in fairness perceptions between the posttest and postdecision stage. Practical implications and an agenda for future research are discussed.
Keywords: 650; applicant; change; fairness; latent trajectory; meta-analysis; perceptions; personnel selection